Vibrotactile Perception in Finger Pulps and in the Sole of the Foot in Healthy Subjects among Children or Adolescents - Dahlin, Lars B.; Güner, Nuray; Elding Larsson, Helena; Speidel, Toni (PloS one, 2015)
To evaluate vibrotactile perception at different frequencies in fingers and in foot in healthy girls and boys. Vibration perception thresholds (VPTs) were measured in 283 healthy (8-20 years), consecutively included, girls (n=146) and boys (n=137); i.e., 269 children after excluding those with diseases or disorders possibly affecting the nervous system. Thresholds were measured in finger pulps of index and little fingers (seven frequencies; 8-500 Hz) and at first and fifth metatarsal head and at heel in the sole of the foot (six frequencies; 8-250 Hz;) using Multi Frequency Tactilometry. VPTs, divided in six groups by age and gender (i.e., 8-10 years, 11-15 years and 16-20 years), at all three sites in the sole increased with higher frequencies, but without gender differences. Thresholds at 64 and 125 Hz were generally higher at heel compared to metatarsal heads. VPTs in finger pulps of index and little fingers, with no finger differences, had a different pattern with increasing thresholds with frequency, but with lower thresholds at 64 and 125 Hz. Thresholds at lower frequencies were higher in finger pulps, while at higher frequencies VPTs were lower in finger pulps than in the sole of the foot; thus, vibration perception in the sole was better than perception in finger pulps at lower frequencies and opposite at higher frequencies. VPTs were higher among adolescents than in younger children in the foot, while thresholds were lower in the finger pulps among adolescents, particularly in index finger. Thresholds in finger pulps of index and little fingers, particularly at higher frequencies, correlated with each other, which the three sites in the sole also did. VPTs in fingers and in feet are different as related to frequency in healthy girls and boys. Multi Frequency Tactilometry is a future valuable method to detect neuropathy in children and adolescents.